Bioaccumulation of Lead Metal (Pb) by Mangrove Plants (Rhizopora apiculata) in the Waters of Poka Village, Inner Bay of Ambon - Mariwy, Abraham; Dulanlebit, Yeanchon H; Ode, A. (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2024)
This research aims to study the extent of bioaccumulation of the heavy metal Pb by mangrove plants (Rhizopora apiculata) in the waters of Poka Village, Ambon Bay. Mangrove plants were chosen because they can naturally accumulate heavy metals around their roots. In this study, sediment grains were measured using a Sieve Shaker, the content of Pb metal in sediment and parts of mangrove plants was determined using AAS, while the bioaccumulation value of Lead metal (Pb) by mangrove plants was calculated using the BCF and TF formulas. The results showed that the particle size in gravel ranged between 0.00-0.13%, sand 20.44-66.35%, and mud 33.65-79.56%. Lead (Pb) levels in Poka Village waters in sediment ranged from 10,925-16,925 mg/kg, roots ranged from 0.5-21.35 mg/kg, and leaves ranged from 0-4,675 mg/kg. Meanwhile, the BCF value at sampling point 1 = 0.03, sampling point 2 = 1.40 and sampling point 3 = 0.56, the TF value at sampling point 1 = 7.8, sampling point 2 = 0.03 and sampling point 3 = 0.09. This shows that mangrove plants function as phytoextraction and can be used as phytoremediation agents to accumulate the heavy metal lead (Pd) from waters.